2014
DOI: 10.1097/wnr.0000000000000151
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution music with inaudible high-frequency components produces a lagged effect on human electroencephalographic activities

Abstract: High-quality digital sound sources with inaudible high-frequency components (above 20 kHz) have become available because of recent advances in information technology. Listening to such sounds has been shown to increase the α-band power of an electroencephalogram (EEG). The present study scrutinized the time course of this effect by recording EEG along with autonomic measures (skin conductance level and heart rate) and facial electromyograms (corrugator supercilii and zygomaticus major). Twenty university stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, the extensive research into brain response to high resolution content suggests that exposure to high frequency content may evoke a response that is both lagged and persistent for tens of seconds, e.g., [22,48]. This implies that effective testing of high resolution audio discrimination should use much longer samples and intervals than the ITU recommendation implies.…”
Section: How Does Duration Of Stimuli and Intervals Affect Results?mentioning
confidence: 97%
“…However, the extensive research into brain response to high resolution content suggests that exposure to high frequency content may evoke a response that is both lagged and persistent for tens of seconds, e.g., [22,48]. This implies that effective testing of high resolution audio discrimination should use much longer samples and intervals than the ITU recommendation implies.…”
Section: How Does Duration Of Stimuli and Intervals Affect Results?mentioning
confidence: 97%
“…In the present study, every participant was exposed to both natural cry sounds with intact ultrasonic components and scrambled cry sounds whose ultrasonic components were destroyed in its frequency structure. Considering the previous studies indicating the unconscious effect of inaudible components on behaviour [45,46] and neural activation [21,22,31], the neural system may have detected subtle "unnaturalness" in the scrambled cries due to a contrast effect induced by the presentation of high-fidelity natural cry sounds. This design might have attenuated physiological responses to scrambled cries in the present study.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that EEG alpha-band (8–13 Hz) frequency power is greater for high-resolution music with high-frequency components than for the same sound sources without them ( Oohashi et al, 2000 , 2006 ; Yagi et al, 2003a ). The effect appears more clearly in a higher part of the conventional alpha-band frequency of 8–13 Hz (10.5–13 Hz: Kuribayashi et al, 2014 ; 11–13 Hz: Ito et al, 2016 ). Ito et al (2016) reported that low beta-band (14–20 Hz) EEG power also showed the same tendency to increase as high alpha-band EEG power.…”
Section: Introductionmentioning
confidence: 96%
“…In contrast to this conventional digital recording process in which inaudible high-frequency components are cut off, high-resolution music that retains such components has been repeatedly shown to affect human electroencephalographic (EEG) activity ( Oohashi et al, 2000 , 2006 ; Yagi et al, 2003a ; Fukushima et al, 2014 ; Kuribayashi et al, 2014 ; Ito et al, 2016 ). This effect is often called “hypersonic” effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation